Influencia de los medios de comunicación audiovisuales locales en la calidad de vida de los habitantes de la Parroquia 7 de Octubre del canton Quevedo, año 2022 - Zarate Beltran, Elizabeth Raquel (2022)
The project whose theme is "Influence of local audiovisual media in the quality of life" was carried out in the Parroquia 7 de Octubre, Cantón Quevedo, province of Los Ríos, was executed with the purpose of analyzing the behavior and development of the inhabitants along with the management of television media as they are learning and evolving over time but depending on how they use them. Therefore a methodology with a qualitative approach to know the result of how much knowledge they have about the media and how they are developing in all social areas in which a questionnaire of questions will be applied to deepen the development and attitudes in the inhabitants of the parish of October 7. Through the analysis of the survey conducted to the inhabitants of the parish of October 7, it was possible to determine several questions that obtained some situations detected and also reached some solutions raised giving conclusions and recommendations to continue with this research project. At present the local audiovisual media are not well seen for not having clear or totally truthful information or simply is not the first option they see and choose other options such as social networks that are implemented videos or news information within the same locality from just a phone with internet. Giving clear the behavior that is showing the development of the inhabitants and how their behaviors are related to the audiovisual media because as they are seeing something on television or social networks they take it very seriously and they are doing it in the life they have in the locality seeing how it affects their social welfare.